A model for evaluating the environmental and functional benefits of "innovative" roundabouts. (August 2015) - Guerrieri, Marco; Corriere, Ferdinando; Lo Casto, Barbara; Rizzo, Gianfranco
Highlights: A criterion for comparing "conventional" with "flower" and "turbo" roundabout is presented. We applied closed-form capacity and delay models for 7 types of roundabouts. Pollutant emissions show different distributions for each roundabout and traffic intensity. Construction, delay, environmental and overall costs are evaluated in many traffic conditions. Abstract: This study looks at the singling out of a multi-parameter criterion for choosing conventional or innovative roundabout layouts, by taking functional, environmental and economic aspects into consideration. The performances of three conventional roundabouts (with different lane number at entries and through the ring), turbo-roundabouts and roundabouts with right-turn bypass lane on all the arms (flower roundabouts) have been compared in terms of vehicle delays and pollutant (carbon dioxide, nitrogen oxides, particle pollution (PM10 and PM2.5 )) emissions. By means of closed-form capacity models and with the help of COPERT IV © software, several traffic simulations have been carried out, referred to yearly peak flow values Qmax and ranging between 1300 and 3300 veh/h, starting from a typical annual traffic demand curve in urban areas. The estimation of cumulative vehicle delays and annual pollutant emissions, together with construction and maintenance costs has allowed working out overall costs for each roundabout under consideration, depending on the traffic demand. Thus, the proposed model allows finding the most cost-effective geometric solution as to overall costs for a comprehensive case record of traffic values.